STATUS OF VIOLATIONS OF THE MINIMUM DISTANCE REGULATION FROM EDUCATIONAL AND HEALTHCARE FACILITIES AMONG TOBACCO RETAIL OUTLETS IN VIETNAM, 2024 (Vietnam Journal of Community Medicine, 2026)
Objectives: To determine the proportion of tobacco retail outlets violating the regulation on the minimum distance of 100 meters from the boundaries of educational and healthcare facilities in Vietnam in 2024, and to assess the knowledge and attitudes of tobacco retailers regarding this regulation.Methods: A cross-sectional descriptive study was conducted at 2,414 tobacco retail outlets across eight provinces and cities in Vietnam from September to December 2024.Results: The study found that 43.5% of retail outlets were located within 100 meters of educational and healthcare facilities in the eight study provinces/cities. The highest proportion of violations was observed near primary schools (13.1%), while the lowest was observed near hospitals (6.4%). In addition to the observed violations of the distance regulation, the study found that retailers’ awareness of this regulation remained low (6.1%). Meanwhile, 73.6% of retailers considered the ban on tobacco sales within 100 meters of educational and healthcare facilities to be necessary. Strengthening communication, dissemination of legal regulations, and monitoring of enforcement is needed to reduce violations.
Keywords: Tobacco Control Law; tobacco; distance violation; schools; healthcare facilities.